2015
DOI: 10.1093/sw/swv017
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault and Depressive Symptoms in College Students: Do Psychological Needs Account for the Relationship?

Abstract: In this study, authors examined basic psychological needs (namely, competence, autonomy, and relatedness) as potential mediators of the association between sexual assault and depressive symptoms in a sample of 342 college students. Results from conducting a multiple mediation test provided support for partial mediation involving the indirect effects of competence and autonomy. In contrast, no support for mediation was found involving relatedness. It is notable that sexual assault remained a significant predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Satisfaction of Basic Psychological Needs Questionnaire: this questionnaire consists of 21 questions and includes three scales of autonomy, competence, and relatedness. This questionnaire is about satisfaction of basic psychological needs in life and higher scores indicate more satisfaction of needs (10). The reliability of this scale was calculated on the basis of the results of the two tests, and the correlation coefficient from 0.67 to 0.77 was approved for different sub-scales.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction of Basic Psychological Needs Questionnaire: this questionnaire consists of 21 questions and includes three scales of autonomy, competence, and relatedness. This questionnaire is about satisfaction of basic psychological needs in life and higher scores indicate more satisfaction of needs (10). The reliability of this scale was calculated on the basis of the results of the two tests, and the correlation coefficient from 0.67 to 0.77 was approved for different sub-scales.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, researches of Smojver-Azic, Dorcic and Zivcic-Becirevic (1), Kormas, Karamali and Anagnostopoulos (9), Houle and Philippe (6), Chang et al (10) and Neubauer and Vos (11) showed that the satisfaction of basic psychological needs has relationship with depression.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is attributed to the stigma of sexual violence and subsequent self-blame (Herman 1992;Jordan et al 2014;Resick 1993). Research has examined sexual violence among college students, along with the psychiatric implications, ranging from depression to dietary disorders (Brewer et al 2018;Carey et al 2018;Chang et al 2015;Kelley and Gidycz 2019;Leone and Carroll 2016;Stephens and Wilke 2016). In the past decade, universities have experienced increased sexual violence reporting rates and Title IX complaints, potentially due to the Obama administration's more proactive stance on Title IX enforcement (Musu-Gillette et al 2017;Wilson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is vital to gage the rate at which individuals are receiving sexual assault education prior to attending college. As multiple scholars have mentioned, women at the ages of 16-24 are at the highest risk of being sexually victimized (Loiselle & Fuqua, 2007;Arnowitz et al, 2012;Chang et al, 2015;Armstrong et al, 2006). It was reported that 70 percent of participants did not receive any high school education on sexual assault or consent.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Women between the ages of 16-24 are also at a greater risk of becoming a victim compared to those who are not within the age range (Loiselle & Fuqua, 2007;Arnowitz et al, 2012;Chang et al, 2015;Armstrong et al, 2006). Traditional students who go on to achieve post-secondary education are within the age range of 16-24.…”
Section: Sexual Assault On College Campusesmentioning
confidence: 99%